Synthesize of pluronic-based nanovesicular formulation loaded with Pistacia atlantica extract for improved antimicrobial efficiency - Al-Ouqaili, Mushtak T.S.; Saleh, Raed Obaid; Amin, Hawraz Ibrahim M.; Jawhar, Zanko Hassan; Akbarizadeh, Majid Reza; Naderifar, Mahin; Issa, Kovan Dilawer; Gavilán, Juan Carlos Orosco; Nobre, Marcos Augusto Lima [UNESP]; Jalil, Abduladheem Turki; Akhavan-Sigari, Reza (Scientific Scholar, 2023)
One of the current concerns to human health is antibiotic resistance, which promotes the use of antibiotics that are more harmful, expensive, and ineffective. In this condition, researchers are turning to innovative options to combat this alarming situation. Combining herbal medicine with nanotechnology has created a new strategy to increase the effectiveness of phytochemical compounds in overcoming antimicrobial resistance. Pistacia atlantica is one of the promising herbs with medicinal benefits, but its poor solubility in biological fluids is challenging. In this regard, we seek to evaluate the antibacterial efficacy of Pistacia atlantica extract-loaded nanovesicle. Cholesterol, Span 40, and Pluronic F127 modified nanoformulation was developed using an environmentally friendly improved heating technique, and it was evaluated for size distribution, zeta potential, morphology, entrapment efficiency (EE%), release behavior, stability, and antimicrobial performance. By using DLS, spherical nanovesicles were identified with a size distribution of 50–150 nm and a zeta potential of −43 mV. The extract's encapsulation efficiency was 72.03%. The developed loaded nanovesicles demonstrated controlled extract release in the tested 96 h and storage stability of at least 12 months at 25 °C. Also, Comparing the two samples, the encapsulated extract had greater antibacterial activity against Candida albicans, Staphylococcus aureus, and Pseudomonas plecoglossicida with MIC of 1320, 570, and 1100 µg/mL, respectively. Besides reducing the misuse of antibiotics by allowing for the controlled release of drugs made from natural sources, we expect the findings described here to help provide alternative plant-based formulations with greater stability and antibacterial activity.
Keywords: Anti-microbial effects; Nanovesicle; Pistacia atlantica extract; Pluronic surfactant